Mineral Deposits in Ficus Leaves: Morphologies and Locations in Relation to Function. Issue 2 (14th December 2017) - Pierantoni, Maria; Tenne, Ron; Rephael, Batel; Brumfeld, Vlad; van Casteren, Adam; Kupczik, Kornelius; Oron, Dan; Addadi, Lia; Weiner, Steve
Abstract : Mineral deposition in Ficus leaves is highly regulated, and some of the minerals function in light distribution to enhance photosynthesis, depending upon the mineral location in the leaf. Abstract: Ficus trees are adapted to diverse environments and have some of the highest rates of photosynthesis among trees. Ficus leaves can deposit one or more of the three major mineral types found in leaves: amorphous calcium carbonate cystoliths, calcium oxalates, and silica phytoliths. In order to better understand the functions of these minerals and the control that the leaf exerts over mineral deposition, we investigated leaves from 10 Ficus species from vastly different environments (Rehovot, Israel; Bologna, Italy; Issa Valley, Tanzania; and Ngogo, Uganda). We identified the mineral locations in the soft tissues, the relative distributions of the minerals, and mineral volume contents using microcomputed tomography. Each Ficus species is characterized by a unique 3D mineral distribution that is preserved in different environments. The mineral distribution patterns are generally different on the adaxial and abaxial sides of the leaf. All species examined have abundant calcium oxalate deposits around the veins. We used micromodulated fluorimetry to examine the effect of cystoliths on photosynthetic efficiency in two species having cystoliths abaxially and adaxially ( Ficus   microcarpa ) or only abaxially ( Ficus   carica ). In F. microcarpa, both adaxial and abaxial cystoliths efficiently contributed to light redistribution inside the leaf and, hence, increased photosynthetic efficiency, whereas in F. carica, the abaxial cystoliths did not increase photosynthetic efficiency.